The Canadian Centre for Ethics in Sport (CCES)
Homepage of the Canadian Centre for Ethics in Sport (CCES) which is a national non-profit organization and strives for a fair and ethical sport system by promoting drug-free sport, equity, fair play, safety and non-violence. The CCES incorporates the mission, mandate and activities of the former Canadian Centre for Drug-free Sport and Fair Play Canada and manages all aspects of athlete drug testing .